Multiple Household Water Sources and Their Use in Remote Communities With Evidence From Pacific Island Countries. Issue 11 (13th November 2017) - Elliott, Mark; MacDonald, Morgan C.; Chan, Terence; Kearton, Annika; Shields, Katherine F.; Bartram, Jamie K.; Hadwen, Wade L.
Abstract: Global water research and monitoring typically focus on the household's" main source of drinking‐water." Use of multiple water sources to meet daily household needs has been noted in many developing countries but rarely quantified or reported in detail. We gathered self‐reported data using a cross‐sectional survey of 405 households in eight communities of the Republic of the Marshall Islands (RMI) and five Solomon Islands (SI) communities. Over 90% of households used multiple sources, with differences in sources and uses between wet and dry seasons. Most RMI households had large rainwater tanks and rationed stored rainwater for drinking throughout the dry season, whereas most SI households collected rainwater in small pots, precluding storage across seasons. Use of a source for cooking was strongly positively correlated with use for drinking, whereas use for cooking was negatively correlated or uncorrelated with nonconsumptive uses (e.g., bathing). Dry season water uses implied greater risk of water‐borne disease, with fewer (frequently zero) handwashing sources reported and more unimproved sources consumed. Use of multiple sources is fundamental to household water management and feasible to monitor using electronic survey tools. We contend that recognizing multiple water sources can greatly improve understanding of household‐level and community‐level climate change resilience, that use of multiple sources confounds health impact studies of water interventions, and that incorporating multiple sources into water supply interventions can yield heretofore‐unrealized benefits. We propose that failure to consider multiple sources undermines the design and effectiveness of global water monitoring, data interpretation, implementation, policy, and research. Key Points: Household use of multiple water sources occurs in many countries but very few studies examine the practice in detail >90% of households in Pacific Islands study sites used two or more water sources for daily needs and most reported changes by season Neglecting multiple household water sources undermines global water monitoring, data interpretation, implementation, policy, and research